A novel method for the determination of tetracycline antibiotics and hydrogen peroxide using anoized boron-doped diamond thin film electrodes - Nattakarn Wangfuengkanagul (Chulalongkorn University, 2013)
Thesis (Ph.D.)--Chulalongkorn University, 2005